Quantum phonon transport in 3D metal-dielectric point polycontacts with strong lattice distortions - Feher, A.; Egupov, S.A.; Shkorbatov, A.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The experimental results and theoretical analysis of the heat flux in an Si-Cu pressure-made 3D point contact are given. The contributions of the quantum phonon transport, weak electron-phonon interactionand strong phonon-lattice distortion scattering to the phonon heat flux are theoretically investigated.